Adhesive film and polarizing plate with adhesive layer
Patent Information
- Application Number
- JP2023102345
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-06-22
- Publication Date
- 2025-03-06
- Estimated Expiration
- 2035-05-07
AI Technical Summary
【0020】 本発明によれば、光学部材の層間の貼合に用いても、表面硬度を維持することが可能で、耐久性、リワーク性も兼ね備えた、粘着剤層及び粘着フィルムを提供することができる。
Smart Images

Figure 0007641326000001 
Figure 0007641326000002 
Figure 0007641326000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a thin pressure-sensitive adhesive layer having a thickness of 1 μm to 20 μm, which is used for bonding between layers of optical components, and to an adhesive film in which this pressure-sensitive adhesive layer is sandwiched between release films. [Background technology]
[0002] In recent years, various display devices, such as smartphones, tablet terminals, and tablet PCs, that have a capacitive touch panel attached to an external liquid crystal panel have been widely used. In such display devices, a physical space exists between the liquid crystal panel and the touch panel. This causes a problem that external light is reflected on the upper surface of the liquid crystal panel and the lower surface of the touch panel, reducing visibility, especially in bright environments such as outdoors.
[0003] As a method for solving the problem of reduced visibility, an in-cell type display device that incorporates touch panel functions into the pixels of the liquid crystal display has been proposed (see, for example, Patent Document 1). However, this has not been put to practical use due to the complex manufacturing process, which reduces product yields, and the technical difficulties of improving image display performance.
[0004] Meanwhile, on-cell type display devices have been proposed recently (see, for example, Patent Document 2). In on-cell type display devices, a touch sensor made of a transparent electrode pattern is formed between a color filter and a polarizing plate, and the function of a touch panel is built in between the color filter substrate and the polarizing plate. The on-cell type has the advantage of less reduction in product yield. For this reason, the on-cell type is expected to develop further as a promising manufacturing technology for liquid crystal panels incorporating touch panels. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2009-258182 A [Patent Document 2] JP 2014-044501 A Summary of the Invention [Problem to be solved by the invention]
[0006] In the above-mentioned various display devices, a pressure-sensitive adhesive layer is generally used to bond layers of optical members together. However, when at least one of the optical members has a surface hardness increased by surface treatment such as a hard coat layer (for example, the surface has a pencil hardness of 2H or more), if the pressure-sensitive adhesive layer used for bonding the optical members is soft and thick, there is a problem that a measurement error occurs when measuring the surface hardness of the laminate to which the optical members are bonded. This is a phenomenon in which, when the hard coat layer of a laminate to which an optical component is bonded is touched with a pencil, even if the surface hardness of the optical component itself is high, the optical component is dented due to the thin base film of the optical component being thinner and therefore less rigid, and the pressure-sensitive adhesive layer being soft, resulting in a lower apparent surface hardness.
[0007] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide an adhesive layer and an adhesive film which, even when used for bonding layers of optical components, does not cause errors in the measured surface hardness of a laminate to which an optical component is bonded, and which also has durability and reworkability. [Means for solving the problem]
[0008] In order to solve the above problems, the present invention has a technical idea of reducing the thickness of the adhesive layer to 1 μm to 20 μm compared to conventional techniques, and at the same time, in order to maintain adhesive strength equivalent to that of conventional adhesive layers even with the thinner adhesive layer, the main component (meth)acrylic monomer contains at least one monomer selected from an acrylic monomer group consisting of an alkyl (meth)acrylate monomer having a carbon number of C1 to C14 in the alkyl group, a (meth)acrylate monomer having an aromatic group, a nitrogen-containing vinyl monomer, and a (meth)acrylate monomer having an alicyclic group, of which at least 40 parts by weight or more of butyl acrylate is contained out of a total of 100 parts by weight, and further, to reduce the corrosiveness of the adhesive layer, the acrylic polymer does not contain a carboxyl group-containing copolymerizable vinyl monomer.
[0009] In order to solve the above problems, the present invention provides a pressure-sensitive adhesive layer used for bonding an optical member, the pressure-sensitive adhesive layer being obtained by crosslinking a pressure-sensitive adhesive composition containing an acrylic polymer and a crosslinking agent, the acrylic polymer comprising: (1) a main component (meth)acrylic monomer, which contains at least 40 parts by weight or more of butyl acrylate out of a total of 100 parts by weight of at least one monomer selected from an acrylic monomer group consisting of an alkyl (meth)acrylate monomer having an alkyl group of C1 to C14, a (meth)acrylate monomer having an aromatic group, a nitrogen-containing vinyl monomer, and a (meth)acrylate monomer having an alicyclic group, and does not contain a carboxyl group-containing copolymerizable vinyl monomer; the acrylic polymer has a Tg of -35°C or more and -10°C or less; the pressure-sensitive adhesive composition comprises a main component (meth)acrylic monomer having a total of 100 parts by weight of at least one monomer selected from an acrylic monomer group consisting of an alkyl (meth)acrylate monomer having a carbon number of C1 to C14, a (meth)acrylate monomer having an aromatic group, a nitrogen-containing vinyl monomer, and a (meth)acrylate monomer having an alicyclic group; and (2) 0.1 to 10 parts by weight of a hydroxyl group-containing copolymerizable vinyl monomer, and (3) 0.01 to 1.0 parts by weight of only an isocyanate compound as a crosslinking agent, relative to a total of 100 parts by weight of the (meth)acrylic monomer as the main component, and further containing 0.01 to 0.5 parts by weight of a silane coupling agent having at least one organic functional group selected from the group consisting of an epoxy group, a (meth)acryloxy group, a mercapto group, and an amino group, the gel fraction after crosslinking the acrylic polymer is 40 to 85%, the thickness of the pressure-sensitive adhesive layer is 1 μm to 20 μm, and the pressure-sensitive adhesive film obtained by transferring a 10 μm-thick pressure-sensitive adhesive layer to one side of a 180 μm-thick polarizing plate film is subjected to a peel test against alkali-free glass in accordance with JIS Z 10245. The adhesive layer is characterized in that the adhesive strength of the resulting adhesive layer having a thickness of 10 μm is 1.5 to 8.0 N / 25 mm and the refractive index of the adhesive layer is 1.47 to 1.50 when the adhesive layer is subjected to a 180° direction at a speed of 300 mm / min in accordance with ISO 20237.
[0010] The pressure-sensitive adhesive composition preferably further contains 0.01 to 0.5 parts by weight of a silane coupling agent.
[0011] The crosslinking agent contained in the pressure-sensitive adhesive composition is an isocyanate compound, and preferably contains at least one selected from the group consisting of a trimethylolpropane adduct of tolylene diisocyanate and an isocyanurate of hexamethylene diisocyanate.
[0012] It is preferable that the (2) hydroxyl group-containing copolymerizable vinyl monomer in the pressure-sensitive adhesive composition is at least one selected from the group consisting of 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 2-hydroxyethyl (meth)acrylate.
[0013] The adhesive film is preferably attached to an alkali-free glass substrate and then stored at 70° C. for 10 days, and the adhesive strength is preferably 10 N / 25 mm or less.
[0014] The present invention also provides a pressure-sensitive adhesive film, characterized in that the pressure-sensitive adhesive layer is formed on one side of a release film, and has a structure of release film / pressure-sensitive adhesive layer / release film.
[0015] The present invention also provides a pressure-sensitive adhesive film comprising the pressure-sensitive adhesive layer laminated on one surface of a substrate.
[0016] The present invention also provides an adhesive film for bonding a polarizing plate to a liquid crystal display panel or an organic electroluminescence display panel, which uses the adhesive film.
[0017] The present invention also provides a polarizing plate with a pressure-sensitive adhesive layer, in which the pressure-sensitive adhesive film is used.
[0018] The present invention also provides a polarizing plate with a pressure-sensitive adhesive layer, in which the pressure-sensitive adhesive film is used and a retardation film having a retardation of λ / 4 and / or λ / 2 is used as a constituent material.
[0019] The present invention also provides a pressure-sensitive adhesive layer-attached optical film, comprising an optical film and the pressure-sensitive adhesive layer laminated on at least one surface of the optical film. Effect of the Invention
[0020] According to the present invention, it is possible to provide a pressure-sensitive adhesive layer and a pressure-sensitive adhesive film that are capable of maintaining surface hardness even when used for bonding layers of optical components, and that also have durability and reworkability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] Hereinafter, the present invention will be described based on preferred embodiments. The pressure-sensitive adhesive layer of the present invention is used between an optical member having a surface pencil hardness of 2H or more and another optical member, and is formed by crosslinking a pressure-sensitive adhesive composition made of an acrylic polymer, the acrylic polymer comprising: (1) a (meth)acrylic monomer as a main component, which contains at least 40 parts by weight or more of butyl acrylate out of a total of 100 parts by weight of at least one monomer selected from an acrylic monomer group consisting of an alkyl (meth)acrylate monomer having an alkyl group of C1 to C14 carbon atoms, a (meth)acrylate monomer having an aromatic group, a nitrogen-containing vinyl monomer, and a (meth)acrylate monomer having an alicyclic group, and does not contain a carboxyl group-containing copolymerizable vinyl monomer; the acrylic polymer has a Tg of -35°C or more; and the pressure-sensitive adhesive composition is The adhesive composition is characterized in that it comprises an acrylic polymer consisting of a copolymer having an acid value of 0.1 or less and a weight average molecular weight of 1,000,000 or more, which is obtained by copolymerizing (100 parts by weight in total of the (meth)acrylic monomers as the main component and (2) 0.1 to 10 parts by weight of a hydroxyl group-containing copolymerizable vinyl monomer, and (3) 0.01 to 1.0 part by weight of an isocyanate compound as a crosslinking agent, relative to 100 parts by weight in total of the (meth)acrylic monomers as the main component, the gel fraction after crosslinking the acrylic polymer is 40 to 85%, the thickness of the pressure-sensitive adhesive layer is 1 μm to 20 μm, the adhesive strength of the 10 μm-thick pressure-sensitive adhesive layer is 1.5 to 8.0 N / 25 mm, and the measured pencil hardness of the surface of the optical member bonded to alkali-free glass via the pressure-sensitive adhesive layer is 2H or more, which is the same as the pencil hardness of the surface of the optical member.
[0022] The acrylic polymer according to the present invention is a copolymer obtained by copolymerizing at least one monomer (main component monomer) belonging to the first monomer group and at least one monomer (functional group monomer) belonging to the second monomer group. As the monomer belonging to the first monomer group, at least one monomer selected from the group consisting of an alkyl (meth)acrylate monomer having an alkyl group with carbon number of C1 to C14, an acrylate monomer having an aromatic group, a nitrogen-containing vinyl monomer, and a (meth)acrylate monomer having an alicyclic group can be used. As the monomer belonging to the second monomer group, at least one hydroxyl group-containing copolymerizable vinyl monomer can be used. In this specification, (meth)acrylate is a general term for acrylate and methacrylate.
[0023] In the pressure-sensitive adhesive composition according to the present invention, examples of the alkyl (meth)acrylate monomer having an alkyl group with a carbon number of C1 to C14 include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, isohexyl (meth)acrylate, heptyl (meth)acrylate, isoheptyl (meth)acrylate, and octyl Examples of the alkyl (meth)acrylate monomer include at least one of ethyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, isoundecyl (meth)acrylate, dodecyl (meth)acrylate, isododecyl (meth)acrylate, tridecyl (meth)acrylate, isotridecyl (meth)acrylate, tetradecyl (meth)acrylate, and isotetradecyl (meth)acrylate. The alkyl group of the alkyl (meth)acrylate monomer may be linear or branched. The acrylic polymer according to the present invention contains butyl acrylate as an essential monomer, and the acrylic polymer preferably contains at least 40 parts by weight, more preferably 50 parts by weight or more, and particularly preferably 60 parts by weight or more of butyl acrylate based on 100 parts by weight of the total of the monomers belonging to the first monomer group.
[0024] In the adhesive composition according to the present invention, examples of the (meth)acrylate monomer having an aromatic group include at least one of benzyl (meth)acrylate, naphthyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxybutyl (meth)acrylate, 2-(1-naphthyloxy)ethyl (meth)acrylate, 2-(2-naphthyloxy)ethyl (meth)acrylate, 6-(1-naphthyloxy)hexyl (meth)acrylate, 6-(2-naphthyloxy)hexyl (meth)acrylate, 8-(1-naphthyloxy)octyl (meth)acrylate, and 8-(2-naphthyloxy)octyl (meth)acrylate. In order to obtain an adhesive layer having a high refractive index, it is preferable to blend at least one of the (meth)acrylate monomers having an aromatic group. The acrylic polymer according to the present invention preferably contains 30 parts by weight or less of a (meth)acrylate monomer having an aromatic group, based on a total of 100 parts by weight of monomers belonging to the first monomer group.
[0025] In the pressure-sensitive adhesive composition of the pressure-sensitive adhesive layer according to the present invention, examples of the nitrogen-containing vinyl monomer include (meth)acrylic monomers containing an amide bond and (meth)acrylic monomers containing an amino group. More specifically, examples of the nitrogen-containing vinyl monomer include cyclic nitrogen-containing vinyl compounds having an N-(meth)acryloyl-substituted heterocyclic structure, such as N-(meth)acryloylmorpholine, N-(meth)acryloylpiperazine, N-(meth)acryloylaziridine, N-(meth)acryloylazetidine, N-(meth)acryloylpyrrolidine, N-(meth)acryloylpiperidine, N-(meth)acryloylazepane, and N-(meth)acryloylazocane; (meth)acrylamide, N- Unsubstituted or monoalkyl-substituted (meth)acrylamides such as methyl(meth)acrylamide, N-isopropyl(meth)acrylamide, and Nt-butyl(meth)acrylamide; N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropylacrylamide, N,N-diisopropyl(meth)acrylamide, N,N-dibutyl(meth)acrylamide, and N-ethyl-N-methyl(meth)acrylamide dialkyl-substituted (meth)acrylamides such as N-methyl-N-propyl (meth)acrylamide and N-methyl-N-isopropyl (meth)acrylamide; dialkylamino (meth)acrylates such as N,N-dimethylaminomethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, N,N-dimethylaminoisopropyl (meth)acrylate, N,N-dimethylaminobutyl (meth)acrylate, N,N-diethylaminomethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, N-ethyl-N-methylaminoethyl (meth)acrylate, N-methyl-N-propylaminoethyl (meth)acrylate, N-methyl-N-isopropylaminoethyl (meth)acrylate, N,N-dibutylaminoethyl (meth)acrylate, and t-butylaminoethyl (meth)acrylate;At least one of N,N-dialkyl-substituted aminopropyl (meth)acrylamides such as N,N-dimethylaminopropyl (meth)acrylamide, N,N-diethylaminopropyl (meth)acrylamide, N,N-dipropylaminopropyl (meth)acrylamide, N,N-diisopropylaminopropyl (meth)acrylamide, N-ethyl-N-methylaminopropyl (meth)acrylamide, N-methyl-N-propylaminopropyl (meth)acrylamide, and N-methyl-N-isopropylaminopropyl (meth)acrylamide; (meth)acrylonitrile, etc. may be mentioned. As the nitrogen-containing vinyl monomer, those that do not contain a hydroxyl group are preferable, and those that do not contain a hydroxyl group and a carboxyl group are more preferable. The acrylic polymer according to the present invention preferably contains a nitrogen-containing vinyl monomer in a ratio of 20 parts by weight or less out of a total of 100 parts by weight of the monomers belonging to the first monomer group.;
[0026] In the pressure-sensitive adhesive composition according to the present invention, the (meth)acrylate monomer having an alicyclic group may be at least one of cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, bicycloheptyl (meth)acrylate, bicyclooctyl (meth)acrylate, dimethylbicycloheptyl (meth)acrylate, dicyclopentanyl (meth)acrylate, etc. As with cyclic alkyl (meth)acrylate monomers, the incorporation of a (meth)acrylate monomer having a saturated alicyclic group in the side chain reduces the polarity of the acrylic polymer, thereby contributing to affinity for low-energy surfaces. The acrylic polymer according to the present invention preferably contains 30 parts by weight or less of the (meth)acrylate monomer having an alicyclic group out of a total of 100 parts by weight of the monomers belonging to the first monomer group.
[0027] The monomers (functional group monomers) belonging to the second monomer group have a functional group capable of reacting with an isocyanate compound used as a crosslinking agent. Examples of such functional groups include hydroxyl groups and carboxyl groups. However, from the viewpoint of avoiding the influence on corrosiveness of a corrodible adherend such as the ITO surface of a transparent conductive film, it is preferable that the acrylic polymer does not contain a carboxyl group-containing copolymerizable vinyl monomer. The acid value of the acrylic polymer is preferably 0.1 or less.
[0028] In the pressure-sensitive adhesive composition according to the present invention, the hydroxyl group-containing copolymerizable vinyl monomer may be at least one of hydroxyl group-containing alkyl (meth)acrylates such as 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, etc., and hydroxyl group-containing (meth)acrylamides such as N-hydroxy(meth)acrylamide, N-hydroxymethyl (meth)acrylamide, N-hydroxyethyl (meth)acrylamide, etc. Among them, it is preferable that the hydroxyl group-containing copolymerizable vinyl monomer is at least one selected from the group consisting of 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate. The acrylic polymer according to the present invention preferably contains 0.1 to 10 parts by weight, more preferably 0.2 to 5.0 parts by weight, and particularly preferably 0.2 to 4.0 parts by weight of a hydroxyl group-containing copolymerizable vinyl monomer relative to 100 parts by weight of the total of the monomers belonging to the first monomer group.
[0029] The polymerization method of the copolymer used as the acrylic polymer is not particularly limited, and a known polymerization method such as a solution polymerization method or an emulsion polymerization method can be used as appropriate. The acrylic polymer preferably contains 50 to 100% by weight of an acrylic monomer such as a (meth)acrylate monomer. In the present invention, the glass transition temperature (hereinafter referred to as Tg) of the acrylic polymer is preferably -35°C or higher. If Tg is less than -35°C, reworkability and durability are reduced, which is not preferable. Furthermore, Tg is more preferably -35°C to -10°C. If Tg exceeds -10°C, the adhesive strength required for the present invention cannot be obtained, which is not preferable. In addition, the weight average molecular weight of the acrylic polymer is preferably 1 million or more, and more preferably in the range of 1 million to 2 million.
[0030] The properties of the pressure-sensitive adhesive composition, such as required physical properties, can be adjusted by blending a crosslinking agent and / or any appropriate additives with the acrylic polymer.
[0031] Examples of the crosslinking agent include at least one polyisocyanate compound such as biuret modified or isocyanurate modified diisocyanates such as hexamethylene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, tolylene diisocyanate, and xylylene diisocyanate, and adducts with trivalent or higher polyols such as trimethylolpropane and glycerin.
[0032] The content of the isocyanate compound used as a crosslinking agent is preferably 0.01 to 1.0 parts by weight based on 100 parts by weight of the total of the monomers belonging to the first monomer group. As the crosslinking agent, only the isocyanate compound may be used. As the isocyanate compound, it is preferable to contain at least one selected from the group consisting of a trimethylolpropane adduct of tolylene diisocyanate and an isocyanurate of hexamethylene diisocyanate.
[0033] The pressure-sensitive adhesive composition preferably further contains a silane coupling agent. Examples of the silane coupling agent include compounds having at least one organic functional group and at least one hydrolyzable group in one molecule, the hydrolyzable group being an alkoxy group or the like bonded to a silicon atom. The silane coupling agent preferably has at least one organic functional group selected from the group consisting of an epoxy group, a (meth)acryloxy group, a mercapto group, and an amino group. Here, the (meth)acryloxy group means an acryloxy group (CH2=CHCOO-) or a methacryloxy group (CH2=C(CH3)COO-).
[0034] Examples of silane coupling agents having an epoxy group include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 5,6-epoxyhexyltrimethoxysilane, 5,6-epoxyhexylmethyldimethoxysilane, 5,6-epoxyhexylmethyldiethoxysilane, and 5,6-epoxyhexyltriethoxysilane. Examples of silane coupling agents having a (meth)acryloxy group include 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, 3-(meth)acryloxypropyldimethylethoxysilane, 3-(meth)acryloxypropyldimethylmethoxysilane, etc. Examples of silane coupling agents having a mercapto group include 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropylmethyldiethoxysilane, 3-mercaptopropyltriethoxysilane, etc. Examples of silane coupling agents having an amino group include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, 3-(methylamino)propyltrimethoxysilane, and 3-(methylamino)propyltriethoxysilane.Furthermore, alkoxy oligomers (silicone alkoxy oligomers) containing the above organic functional groups and oligomerized can also be used as silane coupling agents.
[0035] The content of the silane coupling agent is preferably 0.01 to 0.5 parts by weight per 100 parts by weight of the total of the monomers excluding the hydroxyl group-containing copolymerizable vinyl monomer (monomers belonging to the first monomer group).
[0036] Other optional components that may be appropriately blended include known additives such as antioxidants, antistatic agents, surfactants, curing accelerators, plasticizers, fillers, crosslinking catalysts, crosslinking retarders, curing retarders, processing aids, and antiaging agents. These may be used alone or in combination of two or more.
[0037] The pressure-sensitive adhesive layer according to the present invention can be obtained by applying the pressure-sensitive adhesive composition to a substrate or a release film, and then crosslinking the pressure-sensitive adhesive composition. The gel fraction of the pressure-sensitive adhesive layer after crosslinking is preferably 40 to 85%.
[0038] When the pressure-sensitive adhesive layer according to the present invention is used for bonding between layers of optical members, it is desirable that the pressure-sensitive adhesive layer is thin. The thickness of the pressure-sensitive adhesive layer is preferably 1 μm to 20 μm. Also, the adhesive strength of a 10 μm thick pressure-sensitive adhesive layer is preferably 1.5 to 8.0 N / 25 mm. In general, the adhesive strength of a pressure-sensitive adhesive layer is approximately proportional to the thickness of the pressure-sensitive adhesive layer. Examples of the adherend used in the adhesive strength test include glass plates such as alkali-free glass, resin films, and the like.
[0039] When the pressure-sensitive adhesive layer according to the present invention is used for bonding between layers of optical members, it is desirable that the difference in refractive index between the pressure-sensitive adhesive layer and the optical member is as small as possible in order to reduce the reflection of light at the interface between the pressure-sensitive adhesive layer and the optical member. For this reason, the refractive index of the pressure-sensitive adhesive layer is preferably 1.47 to 1.50.
[0040] The adhesive film of the present invention can be produced by forming the adhesive layer of the present invention on one side of a substrate or a release film. A resin film such as a polyester film can be used as the substrate film used to form the adhesive layer or the release film (separator) to protect the adhesive surface. The substrate film can be subjected to an antifouling treatment using a silicone-based or fluorine-based release agent or coating agent, silica fine particles, or an antistatic treatment by coating or kneading an antistatic agent on the side opposite to the side on which the adhesive layer is formed.
[0041] The release film is subjected to a release treatment with a silicone-based or fluorine-based release agent on the surface that is to be joined to the adhesive surface of the adhesive layer. A "release film / adhesive layer / release film" configuration can be achieved by joining the release-treated surfaces of a release film to both sides of one adhesive layer. In this case, the release films on both sides are peeled off sequentially or simultaneously to expose the adhesive surface, which makes it possible to attach it to an optical member such as an optical film. Examples of optical films include polarizing films, retardation films, anti-reflection films, anti-glare films, ultraviolet absorbing films, infrared absorbing films, optical compensation films, and brightness enhancing films.
[0042] The pressure-sensitive adhesive layer according to the present invention can maintain the surface hardness of the adherend even if the pressure-sensitive adhesive layer is thick, and therefore can be suitably used when at least one of the adherends is an optical member having an increased surface hardness (e.g., a surface pencil hardness of 2H or more) due to a hard coat layer, etc. From the viewpoint of reworkability, it is preferable that the adhesive strength of the pressure-sensitive adhesive layer after being attached to the adherend and then stored at 70°C for 10 days is 10N / 25mm or less.
[0043] The adhesive layer and adhesive film of the present invention can be used for bonding various optical films for peripheral members of liquid crystal display devices mainly including polarizing plates, various optical films for touch panels, various optical films for electronic paper, various optical films for organic EL, etc. Also, the adhesive layer can be laminated on at least one surface of these optical films to form an optical film with an adhesive layer. When the adhesive layer is protected by a release film, the release film is peeled off to expose the adhesive layer as in "optical film / adhesive layer", and the adhesive layer is bonded to another optical film, thereby obtaining a configuration such as "optical film / adhesive layer / optical film" in which the adhesive layer is used for bonding between layers.
[0044] The adhesive film of the present invention is preferably used for bonding a polarizing plate and a display panel. Examples of the display panel include a liquid crystal panel and an organic EL (electroluminescence) panel. The adhesive film of the present invention can be preferably used as an adhesive layer of a polarizing plate with an adhesive layer. A retardation film having a phase difference of λ / 4 or λ / 2 may be used as a constituent material of the polarizing plate. The adhesive layer of the present invention can be used for bonding the retardation film and the polarizing plate. EXAMPLES
[0045] The present invention will now be described in detail with reference to examples.
[0046] <Production of acrylic polymer> [Example 1] Nitrogen gas was introduced into a reactor equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube, and the air in the reactor was replaced with nitrogen gas. Then, 75 parts by weight of butyl acrylate, 25 parts by weight of t-butyl acrylate, 1.0 part by weight of 8-hydroxyoctyl acrylate, and 60 parts by weight of a solvent (ethyl acetate) were added to the reactor. Then, 0.1 parts by weight of azobisisobutyronitrile as a polymerization initiator was dropped over 2 hours, and the mixture was reacted at 65°C for 6 hours to obtain an acrylic polymer solution used in Example 1. [Examples 2 to 5 and Comparative Examples 1 to 3] The acrylic polymer solutions used in Examples 2 to 5 and Comparative Examples 1 to 3 were obtained in the same manner as in the acrylic polymer solution 1 used in Example 1 above, except that the monomer compositions were as shown in Groups (1) and (2) of Table 1.
[0047] <Production of Pressure-Sensitive Adhesive Composition, Pressure-Sensitive Adhesive Layer, and Pressure-Sensitive Adhesive Film> [Example 1] To the acrylic polymer solution of Example 1 produced as described above, 0.2 parts by weight of Coronate HX (isocyanurate of HDI) and 0.05 parts by weight of KBM-803 (3-mercaptopropyltrimethoxysilane) were added and stirred to obtain an adhesive composition of Example 1. This adhesive composition was applied onto a release film (a silicone resin-coated polyethylene terephthalate (PET) film), and then dried at 90° C. to remove the solvent. The adhesive composition was then aged for 7 days in an atmosphere of 23° C. and 50% RH to obtain an adhesive film of Example 1 having an adhesive layer formed by crosslinking the adhesive composition on one side of the release film. [Examples 2 to 5 and Comparative Examples 1 to 3] The pressure-sensitive adhesive films of Examples 2 to 5 and Comparative Examples 1 to 3 were obtained in the same manner as the pressure-sensitive adhesive film of Example 1 above, except that the compositions of the additives were as shown in Groups (3) and (4) of Table 1, respectively.
[0048] [Table 1]
[0049] In Table 1, the total of the monomer group (1) consisting of an alkyl (meth)acrylate monomer having an alkyl group carbon number of C1 to C14, an aromatic (meth)acrylate monomer, a nitrogen-containing vinyl monomer, and an alicyclic (meth)acrylate monomer is calculated as 100 parts by weight. The weight parts are enclosed in parentheses to indicate the addition ratios of the monomers (2) to (4). The monomer group (2) is a monomer group consisting of functional group-containing monomers, that is, hydroxyl group-containing copolymerizable vinyl monomers and carboxyl group-containing copolymerizable vinyl monomers. The monomer group (3) is a crosslinking agent. The monomer group (4) is a silane coupling agent.
[0050] The compound names of the abbreviations of each component used in Table 1 are shown in Table 2. Coronate (registered trademark) HX and L are product names of Nippon Polyurethane Industry Co., Ltd., and KBM-403, KBM-802 and KBM-803 are product names of Shin-Etsu Chemical Co., Ltd. TDI means tolylene diisocyanate, TMP means trimethylolpropane, and HDI means hexamethylene diisocyanate.
[0051] [Table 2]
[0052] <Test methods and evaluation> The release film (silicone resin-coated PET film) was peeled off from the pressure-sensitive adhesive film in Examples 1 to 5 and Comparative Examples 1 to 3 to expose the pressure-sensitive adhesive layer, which was then transferred to one side of a polarizing plate (film).
[0053] <Method of measuring adhesive strength> A 10 μm thick adhesive layer was transferred onto one side of a 180 μm thick polarizing plate (film) to obtain a sample adhesive film (optical film with adhesive layer). The obtained adhesive film was laminated with a pressure roller onto the non-tin side of alkali-free glass that had been washed with acetone, and then autoclaved at 50°C, 0.5 MPa x 20 minutes, and then returned to an atmosphere of 23°C x 50% RH for 1 hour. The peel strength of the adhesive film was then measured using a tensile tester in accordance with JIS Z0237 "Test method for adhesive tapes and adhesive sheets," and the peel strength when peeled in the 180° direction at a speed of 300 mm / min was taken as the adhesive strength of the adhesive layer of the adhesive film (N / 25 mm).
[0054] <Acid value measurement method> The acrylic polymer sample was dissolved in a solvent (a mixture of diethyl ether and ethanol in a volume ratio of 2:1) to prepare a measurement sample. The measurement sample was subjected to potentiometric titration with a potassium hydroxide ethanol solution with a concentration of about 0.1 mol / l using an automatic potentiometric titrator (Kyoto Electronics Manufacturing Co., Ltd., AT-610), and the amount of potassium hydroxide ethanol solution required to neutralize the sample was measured. The acid value of the acrylic polymer was then calculated using the following formula. Acid value = (B × f × 5.611) / S B = Amount (ml) of 0.1 mol / l potassium hydroxide ethanol solution used in titration f=factor of 0.1 mol / l potassium hydroxide ethanol solution S = mass of solids in the sample (g)
[0055] <Method of measuring gel fraction> After aging, the mass of the adhesive layer of the measurement sample before bonding to the polarizing plate was accurately measured, and the sample was immersed in toluene for 24 hours and then filtered through a 200-mesh wire screen. The filtered material was then dried at 100°C for 1 hour, and the mass of the residue was accurately measured to calculate the gel fraction of the adhesive layer (adhesive layer after crosslinking) from the following formula. Gel fraction (%) = mass of insoluble portion (g) / mass of adhesive layer (g) × 100
[0056] <Durability test method> A 10 cm square adhesive film made in the same manner as the adhesive strength measurement method was attached to the non-tin surface of alkali-free glass that had been cleaned with acetone using a pressure roller to create a measurement sample. The measurement sample was left in a specified atmosphere (80°C dry atmosphere or 60°C x 90% RH atmosphere) for 250 hours, then removed to a 23°C x 50% RH atmosphere, and the condition of the adhesive film was visually observed after 1 hour to determine durability. The criteria for visual observation were as follows: ○ The adhesive film does not peel off or foam at all. △: Peeling and bubbling have occurred in some parts of the adhesive film. × Peeling and bubbling have occurred over the entire adhesive film.
[0057] <Reworkability test method> A 10 cm square adhesive film made in the same way as for measuring the adhesive strength was attached to the non-tin side of alkali-free glass in the same way to create a sample, which was then left in an atmosphere of 70°C for 10 days, then taken out into an atmosphere of 23°C and left for 1 hour, after which the adhesive strength of the adhesive film was measured to judge reworkability. The criteria for reworkability were as follows: ○The adhesive strength after 10 days at 70℃ is 1.5~10N / 25mm. △ The adhesive strength after 10 days at 70℃ is greater than 10N / 25mm but less than 20N / 25mm. × The adhesive strength after 10 days at 70℃ is greater than 20N / 25mm (cannot be peeled off).
[0058] <Method of measuring pencil hardness> A sample was prepared by transferring an adhesive layer of a specified thickness (Table 4) onto a polarizing plate having a hard coat layer with a pencil hardness of 2H on its surface. The polarizing plate was attached to alkali-free glass via the adhesive layer of the sample, and then a pencil hardness test of the sample surface was carried out in accordance with the scratch hardness (pencil method) of JIS K5600 to measure the pencil hardness of the hard coat layer surface in the layer structure of "hard coat layer / polarizing plate / adhesive layer / alkali-free glass."
[0059] The evaluation results are shown in Tables 3 and 4. Although the results are not specifically shown, the acid value of the acrylic polymer was 0.1 or less in Examples 1 to 5 and Comparative Examples 2 to 3, which did not use a carboxyl group-containing copolymerizable vinyl monomer. The weight average molecular weight of the acrylic polymer was 1 million or more in all cases.
[0060] [Table 3]
[0061] [Table 4]
[0062] In the adhesive films of Examples 1 to 5, which are adhesive films according to the present invention, the acrylic polymer contains at least 40 parts by weight of butyl acrylate out of a total of 100 parts by weight of the (meth)acrylic monomers as the main component. The acrylic polymers of Examples 1 to 5 do not contain a carboxyl group-containing copolymerizable vinyl monomer, and the Tg of the acrylic polymer is -35°C or higher, the acid value is 0.1 or lower, the weight average molecular weight is 1 million or more, and the gel fraction after crosslinking is 40 to 85%. The pencil hardness of the surface of the polarizing plate attached to the alkali-free glass via the adhesive layer remains 2H even in appearance. This means that if the adhesive film according to the present invention is used, there will be no error in the measurement value of the surface hardness of the laminate to which the optical member is attached. In addition, the adhesive layers of Examples 1 to 5 had an adhesive strength of 1.5 to 8.0 N / 25 mm for a thickness of 10 μm, and also had excellent durability. Furthermore, the adhesive films of Examples 1 to 5 were attached to an adherend, and after storage at 70° C. for 10 days, had an adhesive strength of 10 N / 25 mm or less, and therefore had excellent reworkability. In other words, the adhesive films of Examples 1 to 5 were able to overcome the requirements and problems of the prior art.
[0063] In the adhesive film of Comparative Example 1, the acrylic polymer contained a carboxyl group-containing copolymerizable vinyl monomer, so that the acid value of the acrylic polymer was greater than 0.1. In addition, the adhesive film of Comparative Example 1 did not contain butyl acrylate in the acrylic polymer, and the content of the crosslinking agent was excessive. Perhaps because the Tg of the acrylic polymer was lower than -35°C, the reworkability was somewhat poor and the durability at 60°C x 90% RH was poor. In addition, the pencil hardness of the surface of the polarizing plate attached to the alkali-free glass via the adhesive layer was apparently reduced from 2H to H.
[0064] The adhesive film of Comparative Example 2 did not contain butyl acrylate in the acrylic polymer, the Tg of the acrylic polymer was lower than -35°C, and the content of the crosslinking agent was excessive. In addition, the adhesive strength of the adhesive layer with a thickness of 10 μm was smaller than 1.5 N / 25 mm, the durability at 80°C dry was slightly poor, and the durability at 60°C x 90% RH was poor, probably due to the high gel fraction after crosslinking. In addition, the pencil hardness of the surface of the polarizing plate attached to non-alkali glass via the adhesive layer was apparently reduced from 2H to H.
[0065] The adhesive film of Comparative Example 3 does not contain a hydroxyl group-containing copolymerizable vinyl monomer and a carboxyl group-containing copolymerizable vinyl monomer in the acrylic polymer, so even if a crosslinking agent is used, the gel fraction after crosslinking was 0% (not substantially crosslinked). In addition, the Tg of the acrylic polymer was lower than -35°C, the adhesive strength was very high, and the reworkability and durability were poor. In addition, the pencil hardness of the surface of the polarizing plate attached to the non-alkali glass via the adhesive layer was apparently reduced from 2H to H.
[0066] As described above, the adhesive films of Comparative Examples 1 to 3 were unable to overcome the requirements and problems of the prior art.
Claims
1. A pressure-sensitive adhesive layer formed by crosslinking a pressure-sensitive adhesive composition made of an acrylic polymer, which is used between an optical member having a surface pencil hardness of 2H or more and another optical member, The acrylic polymer (1) contains, as a main component (meth)acrylic monomer, at least 40 parts by weight or more of butyl acrylate out of a total of 100 parts by weight of at least one monomer selected from an acrylic monomer group consisting of an alkyl (meth)acrylate monomer having an alkyl group with a carbon number of C1 to C14, a (meth)acrylate monomer having an aromatic group, a nitrogen-containing vinyl monomer, and a (meth)acrylate monomer having an alicyclic group, and does not contain a carboxyl group-containing copolymerizable vinyl monomer; The acrylic polymer has a Tg of −35° C. or higher; the pressure-sensitive adhesive composition comprises an acrylic polymer having an acid value of 0.1 or less and a weight-average molecular weight of 1,000,000 or more, the acrylic polymer being obtained by copolymerizing (1) a total of 100 parts by weight of the (meth)acrylic monomers as the main component and 0.1 to 10 parts by weight of a hydroxyl group-containing copolymerizable vinyl monomer, and (2) 0.01 to 1.0 part by weight of an isocyanate compound alone as a crosslinking agent, relative to the total of 100 parts by weight of the (meth)acrylic monomers as the main component, and further comprises 0.01 to 0.5 parts by weight of a silane coupling agent having at least one organic functional group selected from the group consisting of an epoxy group, a (meth)acryloxy group, a mercapto group, and an amino group; The acrylic polymer has a gel fraction of 40 to 85% after crosslinking, The thickness of the pressure-sensitive adhesive layer is 1 μm to 20 μm, The pressure-sensitive adhesive layer has an adhesive strength of 10 N / 25 mm or less after being attached to an adherend and then stored at 70° C. for 10 days; An adhesive film characterized in that the adhesive strength of a 10 μm thick adhesive layer is 1.5 to 8.0 N / 25 mm.
2. 10. An adhesive film for bonding a polarizing plate to a liquid crystal display panel or an organic electroluminescence display panel, comprising the adhesive film according to claim 1.
3. A polarizing plate with a pressure-sensitive adhesive layer, comprising the pressure-sensitive adhesive film according to claim 1 .
4. 10. A polarizing plate with an adhesive layer, comprising the adhesive film according to claim 1 and a retardation film having a phase difference of λ / 4 and / or λ / 2 as a constituent material.
Citation Information
Patent Citations
Heat treating furnace
JP1988025484A
Display device and method of driving the same
JP2009258182A
Manufacturing method of on-cell capacitive touch panel substrate, on-cell capacitive touch panel substrate, and display device
JP2014044501A
Optical components, adhesive compositions, and liquid crystal display devices
JP2015525368A
Binder layer and adhesive film
JP2016210873A